Integrating Northern Ireland: Cross‐group friendships in integrated and mixed schools - Blaylock, D; Hughes, J; Wölfer, R; Donnelly, C (Wiley, 2018)
While Northern Ireland strives to build a shared society, the current reality is that everyday experiences are still shaped by division along ethno‐religious lines. This is particularly pronounced in the education system, where more than 92% of pupils attend separate schools. Within the predominantly separate education system, however, exists a small collection of schools which cater to a more heterogeneous pupil body and offer the opportunity for young people from both communities to meet and interact, and potentially develop cross‐group friendships. The present study compares the network‐based cross‐group friendships within two such school types; an integrated and a separate post‐primary school. These schools boast a distinct ethos yet they similarly enrol students from Catholic and Protestant backgrounds. Findings reveal that both schools show a high level of interconnection between pupils; however, the integrated school, with an ethos that openly supports social cohesion, shows a greater tendency towards cross‐group interactions and best friendships than those found within the separate school. In line with contact theory, these findings suggest that it may not be enough to simply create opportunities for intergroup contact but that optimal conditions, such as institutional support, may be a prerequisite for positive relationships to flourish. Implications for educational policies designed to promote greater cross‐community contact are discussed.